Overview of Swimming Pool Sanitation Conditions in Cimahi City Public Swimming Pools in 2024 - Gilang Tri Rizki Al Sunandar; Kahar; Muhamad Iqbal; Agus Somad Saputra (Environmental Research and Planetary Health, 2025)
This study evaluates the sanitation conditions, disinfection practices, and presence of E. coli in Swimming Pool, Cimahi City. Using a descriptive survey method, we assessed water quality and staff behavior. The sample in this study was one of the swimming pools with the most users, which is around 48 people/pool /day.  The data analysis of this study is a descriptive with observation and measurement methods which aims to describe and explain the sanitary conditions of swimming pools, the behavior of swimming pool staff regarding disinfection, and Escherichia coli bacteria. Results showed unqualified free chlorine levels (0 mg/l) and high E. coli counts (6–75 CFU/100 ml). Sanitation practices were rated as unhealthy (72.2%), and staff performance in disinfection was very poor. These findings indicate a need for immediate improvements in pool sanitation to protect public health.